Carbon Fiber Reinforced Polymer Sebagai Perkuatan Lentur pada Balok Beton - Zainurrahman -; Eko Darma; Sri Nuryati (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2020)
Concrete Beams can experience a sudden collapse when overload because of its brittle characteristic. The use of Carbon Fiber Reinforced Polymer (CFRP) on concrete beams externally as external confinement is predicted to improve concrete mechanics properties, increase the ductility and capacity of concrete, and the flexural strength of concrete beams. An experimental study on the reinforcement of concrete beams with Carbon Fiber Reinforced Polymer (CFRP) was carried out to estimate the effectiveness of CFRP on concrete structures as a concrete beam flexural reinforcement material. Two types of concrete beams are provided in this study to test the flexural strengthening effect of the externally bound CFRP composite. First type of concrete beam used for testing is a normal concrete beams, whereas the second tested beam, the CFRP was laminated by coating the beams with Fiber. The dimensions of both types are 15cm x15cm with a length of 55cm footing range. Testing result obtained the compressive strength was 23,29 MPa, flexural strength of normal and CRFP concretes were 33,41 Kg/cm2 and 48,07 Kg/cm2 respectively. It was concluded that the use of CRFP at the concrete beam increases flexural strength up to 44% with the ratio of 143 %.